Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11262-015-1198-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of H3N2 avian influenza viruses isolated from live poultry markets and poultry slaughterhouses in Shanghai, China in 2013

Abstract: Five H3N2 avian influenza viruses (AIVs) were isolated from live poultry markets (LPMs) and poultry slaughterhouses in Shanghai, China in 2013. All viruses were characterized by whole-genome sequencing with subsequent genetic comparison and phylogenetic analysis. The hemagglutinin cleavage site of all viruses indicated that the five strains were low-pathogenic AIVs. Phylogenetic analysis of all eight viral genes showed that the five H3N2 viruses clustered in the Eurasian lineage of influenza viruses. The eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Dequan Yang et al . previously reported that H3N2 isolates from LPMs and poultry slaughterhouses in Shanghai had reassorted with other AIVs, especially the H5 and H7 subtypes, probably in pigeons, domestic ducks, and wild birds 34 . An H3N2 isolate from Anhui, which also showed the highest sequence homology to the H7 AIVs, was presumed to be a reassortant of H3 and H7 AIVs 35 .…”
Section: Discussionmentioning
confidence: 95%
“…Dequan Yang et al . previously reported that H3N2 isolates from LPMs and poultry slaughterhouses in Shanghai had reassorted with other AIVs, especially the H5 and H7 subtypes, probably in pigeons, domestic ducks, and wild birds 34 . An H3N2 isolate from Anhui, which also showed the highest sequence homology to the H7 AIVs, was presumed to be a reassortant of H3 and H7 AIVs 35 .…”
Section: Discussionmentioning
confidence: 95%
“…have circulated and evolved in live poultry markets which was considered to be a prolific source of AIVs in China38. The H3 subtype has a wide range of host, including fowl, canine, horse, cat, canine, swine523394041424344. The H3 subtype can establish infection upon interspecies transmission from avian sources, posing a threat to mammals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 100 years, three subtypes of IAVs adapted to human had resulted in four appalling pandemics: H1N1 in 1918 and 2009, H2N2 in 1957 and H3N2 in 1968234. Moreover, H5, H7, and H9 subtypes had resulted in more than one thousand human infections over the last decade, which dramatically changed the perception and impact of avian influenza viruses in mammals5. For a long period, wild aquatic birds have been considered as the only natural reservoir for influenza A viruses.…”
mentioning
confidence: 99%
“…Secondly, few studies described the precise method of collection of ES. A number of papers did not specify whether the viruses isolated and then utilized for analyses were recovered from ES, or the simultaneously collected LBS (Barman et al., 2019; Kou et al., 2009; Yang et al., 2015). This limited our ability to determine to what extent the collection of environmental samples served in meeting the surveillance objectives.…”
Section: Resultsmentioning
confidence: 99%